Relação entre tamanho corporal e estrutura de comunidade em anfíbios anuros do município de Botucatu/SP - Teixeira, Maria Gorete [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The species coexistence in a given community is possible in function of species resources partitioning, among many other factors. The selective pressures which determine the pattern of occupation by species may be directly related to their morphology. In the present study, we investigated the relationship of body size and morphology of 42 species of anurans with their spatial and temporal distribution. The study hypothesis is that body size influences their habitat and behavior. Morphological characters were analyzed regarding to temporal distribution and to ecological indexes (spatial distribution) using conventional and phylogenetic approaches. The results indicate that smaller species are more abundant than large ones, and that there was no significant variation in of total mass (biomass) when analyzed per size classes. There were constraints in species distribution regarding to size. The principal components analyses revealed morphological relations of length and width that refer to typical anurans body shapes of certain habits and habitats. The analysis of Morisita-Horn showed high temporal overlap on the environment occupation between size classes. Descriptive analyses indicated differences in habitat occupation and habit among frogs of different sizes. The Kruskal-Wallis test indicated no relationship between snout-vent length and the habit of anurans. However, the results indicated that species with different body masses have different habits and abundances. Phylogenetic signal was detected in three of four principal components tested, as well as in four of seven ecological indexes tested. The results indicate that environmental indexes are related to anurans morphology, suggesting that environment type and how it is occupied are good predictors to infer body shape. The results indicated that size, duration and regime of water bodies do not influence size and morphology of adult anurans. These ecological factors may be more ...

A coexistência de espécies em uma determinada comunidade é possibilitada, entre diversos fatores, pela partilha dos recursos disponíveis. As pressões seletivas que determinam o padrão de ocupação pelas espécies podem estar diretamente relacionadas à morfologia das mesmas. No presente trabalho foi investigada a relação do tamanho corporal e da morfologia na distribuição espacial e temporal de 42 espécies de anfíbios anuros. A hipótese do estudo é que o tamanho influencia na ocupação do habitat e no hábito das espécies. Características morfológicas foram analisadas em relação à distribuição temporal e a índices ecológicos (distribuição espacial) utilizando abordagens convencionais e filogenéticas. Os resultados indicam que espécies menores são mais abundantes do que espécies de grande porte e que não houve variação expressiva dos valores de massa total (biomassa) dentro das classes de tamanho ao longo do período de estudo. Houve restrição na distribuição das espécies em relação ao tamanho. A análise de componentes principais evidenciou relações morfológicas de comprimento e largura que remetem às formas corporais típicas de anuros de determinados hábitos e hábitats. A análise de Morisita-Horn indicou alta sobreposição quanto à ocupação temporal do ambiente entre as classes de tamanho. Análises descritivas indicaram diferenças na ocupação de hábitat e no hábito entre anuros de tamanhos diferentes. O teste de Kruskal-Wallis não indicou relação entre o comprimento rostro-cloacal e o hábito dos anuros. No entanto, os resultados indicaram que espécies com diferentes massas apresentam hábitos e abundâncias distintas. Foi detectado sinal filogenético para três dos quatro componentes principais testados, como também para quatro dos sete índices ecológicos testados. Os resultados indicam que os índices ecológicos estão relacionados com a morfologia dos anuros, sugerindo que ...
Keywords: Anuro - Distribuição geográfica; Filogenia; Herpetologia; Anfíbio - Botucatu (SP); Herpetology